2018
DOI: 10.1111/ajco.12864
|View full text |Cite
|
Sign up to set email alerts
|

Dose modifications in adjuvant chemotherapy for solid organ malignancies: A systematic review of clinical trials

Abstract: Toxicities of systemic cancer therapies are often less frequently observed in clinical trials than in clinical practice, due to the careful selection of patients with fewer comorbidities. Although guidelines exist for the estimation of chemotherapy dose, clinical factors like age, comorbid illness and extremes of body habitus are not considered in the method of dose calculation, which can result in significant toxicity. We reviewed the referenced clinical trials from which the evidencebased curative-intent can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
4
0
1
Order By: Relevance
“…The dose intensity is known to be critically important to increase the disease-free and overall survival in patients with potentially curable tumours, such as diffuse B-cell lymphoma or germ cell tumours. However, for ACT used in early breast cancer, colorectal cancer, non-small cell lung cancer (NSCLC) and pancreatic tumours, the decision to commence cytotoxic therapy is not an easy one since, for some patients, ACT may be unnecessary and accompanied by significant, even fatal adverse effects (1).…”
Section: Introductionmentioning
confidence: 99%
“…The dose intensity is known to be critically important to increase the disease-free and overall survival in patients with potentially curable tumours, such as diffuse B-cell lymphoma or germ cell tumours. However, for ACT used in early breast cancer, colorectal cancer, non-small cell lung cancer (NSCLC) and pancreatic tumours, the decision to commence cytotoxic therapy is not an easy one since, for some patients, ACT may be unnecessary and accompanied by significant, even fatal adverse effects (1).…”
Section: Introductionmentioning
confidence: 99%
“…Body surface area is recognized to be poorly associated with lean muscle mass 43 and previous studies including a systematic review have reported an association between sarcopenia and chemotoxicity 15 , 43 45 . Dose modification is common and been reported to be required in 20–62% of patients within colorectal cancer trials 46 . Elderly patients are recognized to have a higher rate of chemotoxicity and furthermore, are typically underrepresented within clinical trials 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Dose modification is common and been reported to be required in 20–62% of patients within colorectal cancer trials 46 . Elderly patients are recognized to have a higher rate of chemotoxicity and furthermore, are typically underrepresented within clinical trials 46 , 47 . A previous study 48 of 318 patients aged 80 years and older reported high levels of dose reduction (41%), therapy discontinuation (32%) and hospitalization (32%).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of patients are excluded from these clinical trials due to their advanced disease, poor physical conditions, and/or co-morbidities [15]. The use and outcome of chemotherapy in these patients can differ both regarding efficacy and safety compared to pre-registration reports from study patients [16]. Furthermore, chemotherapy can be used in other combinations and with other co-medications than previously studied, which might influence the effectiveness and/or safety in these patients.…”
Section: Introductionmentioning
confidence: 99%